Comparative outcomes of swing segment revisions of radiocephalic arteriovenous fistula between endovascular and surgical approaches - Suehyun Park; Sangho Lee; Hyeon Ju Kim; Hyung-Kee Kim; Seung Huh; Deokbi Hwang (PLoS ONE, 2025)
Objective Regarding revision of vascular access (VA), endovascular methods are commonly employed owing to their procedural simplicity, yet their durability remains uncertain. This study aimed to compare clinical outcomes of swing segment (SwS) revision of radiocephalic arteriovenous fistula (RC-AVF) between endovascular and surgical approaches. Materials and methods A retrospective cohort study comparing two groups was conducted at one tertiary hospital in South Korea. A total of 131 patients underwent endovascular or surgical revision of SwS in RC-AVF for the first time after AVF creation between 2016 and 2023. Endovascular and surgical revisions were performed in 114 and 17 patients, respectively (interposition, n = 10; patch angioplasty, n = 5; transposition, n = 1; proximalization, n = 1). Kaplan-Meier survival analysis was used to assess post-intervention primary patency (PP) and post-intervention secondary patency (SP). Multivariable Cox regression analysis was performed to adjust for potential confounders, and a subgroup analysis was conducted based on whether the SwS was in stenosis or occlusion. Results The median minimal diameter of SwS was 1.3 mm in the endovascular group and 1.4 mm in the surgical group, and the median lesion length was 2.5 cm and 4.0 cm, respectively. Twelve-month PP was 63.5% vs 73.7% (endo vs surgical, P = 0.79). While PP did not differ in the stenosis subgroup, the occlusion subgroup showed significantly higher PP after surgical revision ( P = 0.002), with surgery associated with a markedly lower risk of loss of PP events (HR 0.073). Conclusion Surgical revision may be preferentially considered for long-segment occlusive lesions, given its superior early PP and the longer lesions typically associated with occlusions, whereas percutaneous transluminal angioplasty (PTA) remains appropriate for focal or stenotic lesions within the SwS. Consistent follow-up is essential to enable timely interventions, thereby maximizing the functionality of RC-AVF.